1992
DOI: 10.3354/meps091057
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on selected elements in organs of dab Limanda limanda and their relation to fish disease state

Abstract: Dunng the Bremerhaven Workshop, concentrations of Hg, Cd, Pb, Cu and Zn were determined in the liver, kidney, 9111s and muscle of healthy and diseased dab Limanda limanda. The results of this preliminary study indicate relationships between metal concentrations and the state of health of the fish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…Moreover, it was found that Hg concentrations were significantly higher in the liver, muscles, and gills of unhealthy female fish (fUDN) (p < 0.05) than in females without UDN symptoms (fH) (Figure 2). In a similar study [11], but in another fish species (Limanda limanda), higher Hg content was also found in the muscles of diseased specimens (ulcers, symptoms of lymphocytosis or papillomas) compared to healthy specimens.…”
Section: Metal Concentrations In Fish Organs Depending On Sex and Hea...supporting
confidence: 61%
See 2 more Smart Citations
“…Moreover, it was found that Hg concentrations were significantly higher in the liver, muscles, and gills of unhealthy female fish (fUDN) (p < 0.05) than in females without UDN symptoms (fH) (Figure 2). In a similar study [11], but in another fish species (Limanda limanda), higher Hg content was also found in the muscles of diseased specimens (ulcers, symptoms of lymphocytosis or papillomas) compared to healthy specimens.…”
Section: Metal Concentrations In Fish Organs Depending On Sex and Hea...supporting
confidence: 61%
“…It was also found that diseased sea trout fUDN, mUDN) had significantly higher Cd and Hg contents in their kidneys compared with their livers ( Table 3 ). The study cited above [ 11 ] indicated no statistically significant differences in the content of Pb and Cd in organs between healthy and diseased individuals. However, other researchers [ 12 ] found significantly higher Pb content in the muscles and Cd in the muscles and livers of diseased Boulogne dabs compared to healthy fish.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, the North and the Baltic seas are heavily polluted as compared to the White Sea. Polychlorobiphenyls, polycyclic aromatic hydrocarbons, organochlorine pesticides, heavy metals and other contaminants have been found in water, sediments, benthic invertebrates and fishes from the North and the Baltic seas (ICES 1977;Schmidt 1980;Falandysz and Lorenc-Biala 1984;Larsen and Pheiffer 1986;Cofino et al 1992;Protasowicki 1991Protasowicki , 1992Olszewska et al 1994;Mathieson et al 1996;Falandysz et al 1998;Atuma et al 1998;Vuorinen et al 1998;Herut et al 1999;Kress et al 1999;Schmolke et al 1999;Ciereszko 2002;Napierska and Podolska 2005;etc.). This ecological situation is closely connected with the promoted industrial development and intense human activities in these regions.…”
Section: Discussionmentioning
confidence: 99%